THE EFFECTIVENESS OF TOTAL PHYSICAL RESPONSE METHOD (TPR) TO IMPROVE STUDENTS’ VOCABULARY MASTERY FOR ELEVENTH GRADE AT SMKN 1 NGANJUK - Apriliana; Sujono (Universitas PGRI Mpu Sindok, 2025)
Vocabulary mastery is very important in learning English. In reality, there are currently a lot of students who do not know the benefits of learning vocabulary mastery. The first problem is the lack of understanding so that students find it difficult to master vocabulary. The objectives of this research are: 1) To find out the application of vocabulary mastery learning strategy 2) To analyze students’ ability in English 3) To describe the vocabulary with total physical response method for eleventh grade students of SMKN 1 Nganjuk in the academic year 2023/2024. The results showed that the application of vocabulary mastery using the total physical response method in learning in class XI SMKN 1 Nganjuk was very helpful. This can also be seen in the average value of the pre-test with a sufficient category of63.47 and the average post-test of96.66. Based on the results of the analysis with a significant level of 5%, the value of tcount (15.54) ttable (1.690) so is counted. This means there are effective in students learning before and after using TPR Method to improve vocabulary mastery on subject matter in class XI students of SMKN 1 Nganjuk.